Răspuns:
a) x=2;y=-1; b) x=3;y=2
Explicație pas cu pas:
sumă de doi radicali; radicalul întotdeauna pozitiv
=> ambii radicali au valoarea 0
a)
√(x - 2)² + √(y + 1)² = 0
|x - 2| + |y + 1| = 0
x - 2 = 0 => x = 2
y + 1 = 0 => y = -1
b)
√(2x - y - 4) + √(x - 3y + 3) = 0
[tex]\begin{cases} 2x - y - 4 = 0\\ x - 3y + 3 = 0\end{cases} \iff \begin{cases} 2x - y = 4 \\ x - 3y = -3 \ \ |\cdot (-2)|\end{cases}[/tex]
[tex]\begin{cases} 2x - y = 4 \\ -2x + 6y = 6\end{cases}[/tex]
[tex]5y = 10 \implies \bf y = 2[/tex]
[tex]x - 6 = - 3 \implies \bf x = 3[/tex]